2016
DOI: 10.1101/gad.276964.115
|View full text |Cite
|
Sign up to set email alerts
|

Targeted cell elimination reveals an auxin-guided biphasic mode of lateral root initiation

Abstract: To sustain a lifelong ability to initiate organs, plants retain pools of undifferentiated cells with a preserved proliferation capacity. The root pericycle represents a unique tissue with conditional meristematic activity, and its tight control determines initiation of lateral organs. Here we show that the meristematic activity of the pericycle is constrained by the interaction with the adjacent endodermis. Release of these restraints by elimination of endodermal cells by single-cell ablation triggers the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
85
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 52 publications
6
85
0
6
Order By: Relevance
“…The priming mechanism described here fits well with earlier experimental observations demonstrating the importance of auxin transport [De Smet et al, 2007,Laskowski et al, 2008,Marhavý et al, 2013, Marhavý et al, 2014, Marhavý et al, 2016 and of auxin signaling in the vasculature [Dubrovsky et al, 2008, Goh et al, 2012 for LR priming, as well as with research demonstrating the impact of IBA production on the amplitude, and to a lesser extent the frequency of priming oscillation [Xuan et al, 2015, Xuan et al, 2016. According to our model, blocking auxin transport will abolish the reflux loop and hence the existence of a proper auxin loading domain, while blocking auxin signaling will abolish events downstream of auxin loading.…”
supporting
confidence: 90%
“…The priming mechanism described here fits well with earlier experimental observations demonstrating the importance of auxin transport [De Smet et al, 2007,Laskowski et al, 2008,Marhavý et al, 2013, Marhavý et al, 2014, Marhavý et al, 2016 and of auxin signaling in the vasculature [Dubrovsky et al, 2008, Goh et al, 2012 for LR priming, as well as with research demonstrating the impact of IBA production on the amplitude, and to a lesser extent the frequency of priming oscillation [Xuan et al, 2015, Xuan et al, 2016. According to our model, blocking auxin transport will abolish the reflux loop and hence the existence of a proper auxin loading domain, while blocking auxin signaling will abolish events downstream of auxin loading.…”
supporting
confidence: 90%
“…Recent findings suggest that mechanical interactions between the pericycle and overlaying endodermis prevent general, widespread pericycle cell cycle activation and that an elevated auxin response is required to overcome these constraints and enable lateral root initiation (Vermeer et al, 2014;Marhavý et al, 2016). In addition, an elevated auxin response is necessary for reorientation of subsequent divisions to generate correct lateral root primordia development (Marhavý et al, 2016).…”
Section: Function Of Primingmentioning
confidence: 99%
“…Recent findings suggest that mechanical interactions between the pericycle and overlaying endodermis prevent general, widespread pericycle cell cycle activation and that an elevated auxin response is required to overcome these constraints and enable lateral root initiation (Vermeer et al, 2014;Marhavý et al, 2016). In addition, an elevated auxin response is necessary for reorientation of subsequent divisions to generate correct lateral root primordia development (Marhavý et al, 2016). Because lateral root initiation takes place in a region of the root that has a low level of auxin response (Dubrovsky et al, 2006(Dubrovsky et al, , 2011, it has been suggested that the primary function of lateral root priming is to produce regularly inter spaced patches of cells with an enhanced capacity to respond to auxin, thereby conditioning these cells to respond to auxin levels to which surrounding pericycle cells are insensitive (Van Norman et al, 2013) and enabling them to start the divisions necessary for lateral root initiation.…”
Section: Function Of Primingmentioning
confidence: 99%
See 2 more Smart Citations